RELIGION, POWER, REASON: A LEGAL AND PHILOSOPHICAL REFLECTION - Andrés, OLLERO (Anales Universitatis Apulensis Series Jurisprudentia; No 15 (2012): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2010)
The dual decision by the European Supreme Court on Human Rights in the case of Lautsi against Italy has become emblematic of the difficulty that Europe has been going through when it comes to setting the role of religion in the public sphere. The decision of the first instance opted unanimously for the mandatory prohibition of displaying the Cross in Italian public schools. Who would dare to impinge on the required neutrality of State in a pluralistic society with regard to comprehensive doctrines of belief or reason? The latter decision of the Court [1] held that the cultural importance of the crucifix rather than its indoctrinating dimension would make the State´s decision to maintain them acceptable. Should Europe instantiate its neutrality in such a surrealist way as to obligate the Scandinavian States to eliminate the cross from their flags? Keywords: European Supreme Court on Human Rights, the role of religion, public sphere, neutrality of State, pluralistic society. [1] From March 18th,  2011 (Requête nº 30814/06)